2020
DOI: 10.1161/circheartfailure.119.006666
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Quality of Life With an Ambulatory Counterpulsation Pump in Advanced Heart Failure Patients

Abstract: Background: The NuPulseCV intravascular ventricular assist system (iVAS) provides extended duration ambulatory counterpulsation via a durable pump placed through the distal subclavian artery. Methods: We performed a prospective, single-arm, multicenter, US Food and Drug Administration-approved feasibility trial of iVAS therapy as a bridge to transplant or decision following the FIH (First-In-Human) trial. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…This treatment, which has been employed in patients with advanced HF eligible to HT with acceptable short-term outcomes, combines the advantages of aortic counterpulsation with the possibility of outof-hospital ambulatory support. 99 The ongoing feasibility study (REGISTRATION: URL: https://www. clinicaltrials.gov; Unique identifier: NCT02645539) will enrich our knowledge on safety and efficacy of this device and possibly also on the long-term effects of counterpulsation.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This treatment, which has been employed in patients with advanced HF eligible to HT with acceptable short-term outcomes, combines the advantages of aortic counterpulsation with the possibility of outof-hospital ambulatory support. 99 The ongoing feasibility study (REGISTRATION: URL: https://www. clinicaltrials.gov; Unique identifier: NCT02645539) will enrich our knowledge on safety and efficacy of this device and possibly also on the long-term effects of counterpulsation.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…There was one mortality and one CVA during this study period [ 16 ]. Interestingly, the NuPulse iVAS is a successor to the Kantrowitz CardioVAD [ 17 ], which was plagued by air embolism and stroke after 4 to 6 months of implant. If anything, the iVAS experience is very similar, suggesting that the use of compressed air beyond a few weeks is potentially dangerous in terms of air-embolism risk.…”
Section: Other Devicesmentioning
confidence: 99%
“…Temporary MCS in the ambulatory setting is an area of investigation intended to facilitate physical rehabilitation and allow outpatient support while the patient awaits cardiac recovery or more definitive therapy. The Intravascular Ventricular Assist System (iVAS; NuPulse) 99 is an extended use, minimally invasive, ambulatory IABP intended to be used as a bridge to transplantation. The initial feasibility trial demonstrated early positive experiences with the device 100 , and larger investigations are underway.…”
Section: Future Developmentmentioning
confidence: 99%